Challenges in the Design and Implementation of The Multicenter Uveitis Steroid Treatment (MUST) Trial – Lessons for Comparative Effectiveness Trials - Holbrook, Janet T. (2011)
BACKGROUND: Randomized clinical trials are an important component of comparative effectiveness (CE) research because they are the optimal design for head-to-head comparisons of different treatment options. PURPOSE: To describe decisions made in the design of the Multicenter Uveitis Steroid Treatment (MUST) Trial to ensure that the results would be widely generalizable. METHODS: Review of design and implementation decisions and their rationale for the trial. RESULTS: The MUST Trial is a multicenter randomized controlled comparative effectiveness trial evaluating a novel local therapy (intraocular fluocinolone acetonide implant) versus the systemic therapy standard of care for noninfectious uveitis. Decisions made in protocol design in order to broaden enrollment included allowing patients with very poor vision and media opacity to enroll and including clinical sites outside the US. The treatment protocol was designed to follow standard care. The primary outcome, visual acuity, is important to patients and can be evaluated in all eyes with uveitis. Other outcomes include patient-reported visual function, quality of life, and disease and treatment related complications. LIMITATIONS: The trial population is too small for subgroup analyses that are of interest and the trial is being conducted at tertiary medical centers. CONCLUSION: CE trials require greater emphasis on generalizability than many RCTs but otherwise face similar challenges for design choices as any RCT. The increase in heterogeneity in patients and treatment required to ensure generalizability can be balanced with a rigorous approach to implementation, outcome assessment and statistical design. This approach requires significant resources that may limit implementation in many RCTs, especially in clinical practice settings.